2014
DOI: 10.1016/j.jval.2014.08.979
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and Management of Medicine Shortages in Belgium, France and from The Perspective of the European Union

Abstract: Objectives: Medicine shortages are a global phenomenon. A growing number of reports indicate the problem is increasingly affecting the European pharmaceutical market. The present study aims to investigate the characteristics, determinants, legal aspects and management of medicine shortages in Belgium, France and from the perspective of the European Union. MethOds: A review of scientific and grey literature was performed. The legal framework on European and national level was reviewed. Primary qualitative data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In the USA, 168 products were listed short due to manufacturing issues 60. Multiple previous studies have reported manufacturing hurdles as one of the reasons of unavailability of medicine in the market 34 38 39 61…”
Section: Discussionmentioning
confidence: 99%
“…In the USA, 168 products were listed short due to manufacturing issues 60. Multiple previous studies have reported manufacturing hurdles as one of the reasons of unavailability of medicine in the market 34 38 39 61…”
Section: Discussionmentioning
confidence: 99%
“…This was also acknowledged by the World Health Organization, which stated that there are more appropriate pricing mechanisms for off-patent medicines than ERP (18). Similarly, most scientific articles reviewing shortages of generic medicines identify cost-containment measures and policies as the underlying root cause (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33).…”
Section: Economical Aspects Of Shortagesmentioning
confidence: 99%